Association of anticardiolipin antibody and C677T in methylenetetrahydrofolate reductase mutation in women with recurrent spontaneous abortions: a new path to thrombophilia? - Couto, Egle; Barini, Ricardo; Zaccaria, Renata; Annicchino-Bizzacchi, Joyce Maria; Passini Junior, Renato; Pereira, Belmiro Gonçalves; Silva, José Carlos Gama da; Silva, João Luiz Pinto e (São Paulo Medical Journal, 2005)
CONTEXT: Recurrent spontaneous abortion (RSA) has been associated with venous throm- bosis in the mother. Acquired and inherited thrombophilia factors are possible causes. OBJECTIVE: To evaluate the association between thrombogenic factors and recurrent spontaneous abortion. TYPE OF STUDY: Case-control study. SETTING: Centro de Atenção Integral à Saúde da Mulher, Universidade Estadual de Campinas. METHODS: 40 ml of blood was collected from 88 women attending an RSA clinic and 88 fertile women attending a family planning clinic, to evaluate the presence of acquired and inherited thrombophilia factors. Anticardiolipin antibodies (ACA), lupus anticoagulant and deﬁciencies of proteins C and S and antithrombin III were evaluated by enzyme-linked immunosorbent assay (ELISA), dilute Russell Viper Venom time (dRVVT), coagulometric and chromogenic methods. DNA was ampliﬁed by the polymerase chain reaction (PCR) to study factor V Leiden and G20210A mutations in the prothrombin gene and C677T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene. Data were analyzed using odds ratios and a regression model for age adjustment. Fisher’s exact test was used to evaluate statistical relationships between associated factors and RSA. RESULTS: ACA was detected in 11 women with RSA and one fertile woman. Heterozygous C677T was detected in 59 women with RSA and 35 fertile women. Concomitant presence of ACA and C677T was found in eight women with RSA and no fertile women (p < 0.01). DISCUSSION: The meaning of the association between C677T mutation in the MTHFR gene and ACA is still not clear. It is possible that an inherited factor that alone would not strongly predispose a woman to thrombosis could, when associated with an acquired factor, start the process and increase the likelihood of thrombosis expression. CONCLUSIONS: ACA and C677T in the MTHFR gene are statistically associated with RSA. The association of these two conditions is a new ﬁnding in thrombogenic factors and RSA.